Thermally induced metastability of InGaAs single-layer for highly strained superlattices by metal-organic chemical vapor deposition - Kang, Sooseok; Kim, Jongmin; Jang, Chan Wook; Jang, Hyunchul; Lee, Sang Tae; Lee, Byeong-hyeon; Kim, Shinkeun; Shin, Chan-Soo; Jun, Dong-Hwan (Elsevier BV, 2022)
In this study, the metastability of In0.68Ga0.32As layers on InP substrates was investigated at various growth temperatures. The thickness of each metastable In0.68Ga0.32As layer was 40 nm, which is four times the critical thickness of the stable lattice with a stress of approximately 1%. The surface morphologies and roughness of the metastable In0.68Ga0.32As layers were highly sensitive to the growth conditions. Cross-hatches were observed on their surfaces when they were grown at various growth temperatures, and over this range, the surface roughness varied from 0.11 nm to 0.16 nm. The lowest surface roughness of 0.11 nm was achieved at 770 °C, and the metastable In0.68Ga0.32As layer showed a flat surface morphology with terraces parallel to the step edges. These results corresponded to those of the strain relaxation analysis of the metastable In0.68Ga0.32As layers using X-ray diffraction spectra. The In0.68Ga0.32As layer grown at 770 °C was almost fully strained, whereas those grown at other growth temperatures were relieved by approximately 10%. The flat surface morphologies and almost fully strained lattices suggested that the growth conditions were suitable for preparing high-quality superlattices with well-defined interfaces. The intuitive results of the metastable In0.68Ga0.32As single layers were utilized to grow high-quality In0.67Ga0.33As/Al0.64In0.36As superlattices with a reduction in the misfit dislocation by 41.8%. The results obtained herein suggest that the growth conditions for superlattices can be easily and efficiently optimized using the metastability of the materials. ？ 2022